Biomass production and nutrient uptake of Chromolaena odorata as compared with other weeds in a burned and a mulched secondary forest clearing planted to plantain (Musa spp. AAB) - Mekoa, C.; Hauser, S. (Wiley, 2009)
Chromolaena odorata (Siam weed; Asteraceae), is an important weed in most cropping systems of humid West and Central Africa. In plantain (Musa spp.), the most important cash food crop in Cameroon, the traditional system of slash and burn of old secondary forest with long phases of weed-free crop growth can no longer be maintained due to invasion by C. odorata. This study evaluated the effects of burning versus mulching biomass after forest clearing on C. odorata biomass production, nutrient uptake and its competition with all other volunteer plants. Weed biomass was sampled before each slashing over 3 years in a plantain field established in secondary forest. Total weed biomass and C. odorata biomass were unaffected by biomass management. Biomass production increases of C. odorata over time were larger after burning than when biomass was retained. Biomass production of trees and broad-leaved plants (other than C. odorata) declined over time. Chromolaena odorata contributed up to 91% of the total volunteer biomass. Nutrient uptake by C. odorata was promoted by burning. Biomass management after forest clearing does not offer an option to slow down invasion by, or reduce growth of C. odorata.